Light Localization and Principal Mode Propagation in Optical Fibers - Nolan, Daniel A.; Nguyen, Dan T. (Frontiers in Physics, 2021)
Optical communication continues to be a major component of the Optical Sciences over 50 years. As a result, advancements in light wave science continues at a rapid pace. A commercial driver is the need to communicate at faster speeds, over longer distances and with greater global connectivity. This demand is ever increasing due to societies demand for more rapid global communication Optical fiber communication relies on the propagation of optical pulses in only one single guided mode. The ability to simultaneously propagate pulses in tens of other guided modes is possible enabling a hundred - fold capacity increase. However light scattering among these simultaneously propagating pulses can rapidly deteriorate signal quality to the point that no signal can be extracted. Principal mode propagation provides a means to overcome this signal deterioration by enabling light localization at the output of the fiber. This methodology brings together two important scientific frontiers, optical communication and the light localization. In this paper, we review this methodology as it relates to optical communication capacity, but also as it relates to light localization. We also review the characterization of these modes both theoretically and experimentally.